East-west approaches to wisdom: thinking and practice in the knowledge economy - Dickie, Laurence; Dickie, Carolyn (Irish Academy of Management, 2007)
The current paper is used to address a range of issues associated with the concept of the 'pyramid of wisdom' to enable progressive organisations to implement knowledge management systems that capture and apply personal and organisational intellect. A brief examination of what constitutes wisdom in the Western and Eastern traditions is followed by a series of hierarchies associated with a postulated model of the pyramid of wisdom. It is argued that understanding the development of wisdom in an organisation can lead to new approaches to strategic reflection, to alternative notions of leadership and to more holistic and democratic ways of expressing authority. Without understanding of, and practice within, the pyramid of wisdom, the personal and organisational roads to success are likely to be bleak, illusions overpowering and accomplishments short-lived.